UJI AKTIVITAS ANTIBAKTERI MADU PAHIT PELAWAN TERHADAP BAKTERI Staphylococcus aureus - Eva Dewi Rosmawati Purba (Jurnal Ilmiah JOPHUS : Journal Of Pharmacy UMUS, 2023)
Honey can be efficacious in curing various diseases. Based on research results, honey contained alkaloid, flavonoid, triterpenoid, phenolic, and glycoside. Those compound that act as antibacterial agents were flavonoid, phenolic, and terpenoid. This study aimed to determine the antibacterial activity of Pelawan Bitter Honey on the growth of the Staphylococcus aureus bacteria that causes wounds. This research was experimental and measures the diameter of the inhibition zone for bacterial growth in Staphylococcus aureus. This research was conducted using nine concentrations of Pelawan Bitter Honey with concentrations of 10% w/v, 20% w/v, 30% w/v, 40% w/v, 50% w/v, 60% w/v, 70% b/v, 80% b/v, and 90% b/v; Belitong Bitter Honey as a positive control with concentrations of 10% w/v, 20% w/v, 30% w/v, 40% w/v, 50% w/v, 60% w/v, 70% w/v, 80% w/v and 90% w/v; aqua dest as a negative control. Extracts that had an inhibition zone as an antibacterial are characterized by the presence of a clear spot around the disc paper. The Kruskal-Wallis test yields was a significant value of 0.000 p-value (0.05), indicating that the concentration of Pelawan Bitter Honey had a significant effect on the growth of Staphylococcus aureus bacteria.